Green Bond in Sustainable Economy: Example of Turkey - DAĞIDIR ÇAKAN, CANAN (My University, 2022)
Global warming is one of the most critical problems nowadays. The environmental, economic, and social dimensions of climate changes caused by global warming affect many different segments. Multilateral cooperation is required to iron out this issue. It is seen that countries, institutions and people have taken the initiative to settle the global warming problem for the last twenty years. However, global warming is not an issue that can be solved by individual behavioral changes. The solution to this problem needs a large amount of labor and costs and requires investment in various infrastructure, technology, and know-how. One method of financing these investments is issuing green bonds. There are still more steps to be taken by our country in the green bond application, which has developed quite rapidly in the world and continues to develop rapidly. Green bonds are a significant resource in ensuring a sustainable economy in our country. It is obvious that green bonds, which are currently only a few in number in our country, will be issued in much larger quantities and volumes in the future. Green bonds will create a strong window of opportunity in order to implement a sustainable economy, to provide cost-effective domestic and foreign resources to our country, and to prevent obstacles that may arise in the export channel in the coming days. For this reason, it is necessary to understand the importance of green bonds and create awareness on the subject. In this study, a green bond application, which was issued for the first time by the real sector in our country in May 2021, was included, the characteristics of green bonds were detailed, the general evaluation of the financing provided by this method and the comparison of the mentioned bond with various green bonds were made. Keywords: Green Bond, Sustainable Economy, Enviromental Economics.
Keywords: Green Bond; Sustainable Economy; Enviromental Economics